Making Good Decisions: Media and the Physical Health of Young Children, A Parent's Tip Sheet - Stephanie C. Toelle; David C. Diehl (EDIS)
FCS-2294, a 3-page tip sheet by Stephanie C. Toelle and David C. Diehl, is part of the Making Good Decisions: Media in the Lives of Young Children series. It lists key findings, things parents can do to help maintain healthy weight in young children, and several internet resources. Published by the UF Department of Family Youth and Community Sciences, February 2009.